Reappraisal of early CT signs to predict the arterial occlusion site in acute embolic stroke - Koga, M (BMJ Group, 2003)
Patients: 105 consecutive patients with acute embolic stroke affecting the anterior circulation. Methods: Four early signs were evaluated on cranial CT within six hours of stroke onset: loss of the insular ribbon (LIR); attenuation of the lentiform nucleus (ALN); hemispherical sulcus effacement (HSE); and the hyperdense middle cerebral artery sign (HMCAS). The arterial occlusion site was definitively identified on cerebral angiography within two hours of the CT examination. Results: LIR was present in 55% of patients with internal carotid artery occlusion. ALN was present in 65% of patients with occlusion of the sphenoidal portion (M1) of the middle cerebral artery. HSE was present in 47% of patients with middle cerebral artery branch occlusion. LIR was related independently to internal carotid artery occlusion (odds ratio (OR) 2.8 (95% confidence interval, 1.2 to 6.8)), ALN to M1 occlusion (OR 2.9 (1.2 to 7.4)), and isolated HSE without ALN or LIR to branch occlusion (OR 12.8 (3.2 to 51.5)). The combined presence of the three signs was indicative of internal carotid artery occlusion (p < 0.05), and the presence of ALN and LIR without HSE was indicative of M1 occlusion (p < 0.05) by univariate analysis. HMCAS bore no relation to either arterial occlusion site. Conclusions: LIR, ALS, HSE, and combinations of these were useful predictors of the arterial occlusion site.